Competitive Intelligence and Small Business Sustainability in a Precarious Working Environment: Evidence from Selected Cleaning Services Companies in Lagos State - Ekwoaba , J. O.; Uwem, Emmanuel (Unilag Journal of Humanities, 2019)
Small businesses are continuously seeking for better insight for their capacity to compete effectively due to competitive pressures from new sources and faster dissemination of both innovation and imitation facilitated by forces of globalisation. However, various studies have shown that most small businesses in Nigeria experience inconsistency in service delivery, employment stability and barely survive a few years after inception. This is a threat to economic growth as small businesses account for about over 50% of GDP of any country. Advancing adequate reasons for small business failure in Nigeria has posed a serious challenge over the years. This study aimed at examining the effect of competitive intelligence on small business sustainability in selected cleaning services companies in Lagos State. A survey research design, stratified sampling technique and simple regression analysis were used for this study. A well-structured questionnaire was administered to the respondents who consist of top executives, supervisors and cleaners working in the selected cleaning services companies in the three senatorial districts (Lagos Central and Lagos East districts consisting of five local government areas, while Lagos West district consist of ten local government areas) in Lagos State and offering janitorial services only. A sample size of 400 respondents was arrived at using a Rao soft sample size calculator out of the total population of 1535 personnel. The hypotheses were tested using simple linear regression. Statistical analysis was carried out using SPSS. The study found that competitive intelligence had a significant effect on small business sustainability in the selected cleaning services companies in Lagos State (B=0.606; R2= .357; p<0.05). The study recommended implementation of organisational justice as panacea for retaining quality human capital capable of sourcing the requisite information needed for strategic decision making and business sustainability. In addition, businesses should adopt human resource policies and practices that could elicit information from both the internal and external environment.